SUBORDINASI PERAN SOSIAL PEREMPUAN (ANALISIS TERHADAP CERPEN â€œLAILAâ€ KARYA PUTU WIJAYA) - Ida Novianti (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Todays, violence and subordination experienced by women in the domestic sphere into the events that are familiar ineveryday life. The Government has been providing products Law Number 23 Year 2004 on the Elimination of Violence in Household.However, this law has not effectively curb the violence that occurs in women. This social reality portrayed by Putu Wijaya in a short story toopen the eyes of the community that the events portrayed in the short story "Laila" is a reflection of the circumstances that exist in thecommunity. Husband-wife relationship is structured, imposition of the will, the absence of living, economic extortion, physical violence andmental, are the kinds of unfair treatment that often befall women.